Characterization of bunt isolates collected from dry temperate zone of Himachal Pradesh - and A.K. SOOD, PREETI AGGARWAL* (Indian Phytopathology, 2006)
Seven isolates of hill bunt (common bunt) were collected from dry temperate zone (Lahaul-Spiti and Kinnaur districts) of Himachal Pradesh and were found to comprise of Tilletia foetida (5 isolates) and T. caries (2 isolates). They were characterized on the basis of their reaction on fifteen monogenic bunt differentials (Bt1 to Bt15). Bt0 and CPAN 1922 were included as universal and local susceptible checks, respectively. Based on virulence/avirulence reaction, the seven isolates were differentiated into six distinct pathotypes and designated as L-1, L-A, L-G, L-11, T-C and T-D. The pathotypes L-G and L-H constituted new virulences of T. foetida whereas T-C and T-D were new virulences of T. caries. The pathotypes L-A, L-G and T-C were found to be more aggressive as compared to others on Bt0 and CPAN 1922. A perusal of literature showed that the majority of population of T. foetida and T. caries existing in northwestern Himalayan region of India are different from those present in northern America.